Численные оценки электродинамических процессов в индукторной системе с притягивающим экраном и плоским прямоугольным соленоидом - Чаплыгин, Евгений Александрович; Барбашова, Марина Викторовна; Коваль, Анжелика Юрьевна (НТУ "ХПИ", 2018)
Проведены численные оценки и анализ полученных результатов для токов и сил в исследуемой индукторной системе с притягивающим экраном и прямоугольным соленоидом. Выявлено, что при уменьшении глубины вмятины в металле, амплитуда, возбуждаемых электродинамических усилий, растёт. Анализ показал, что значение сил отталкивания, интегральное во времени, ниже развиваемых сил притяжения. При достаточно низких рабочих частотах действующих полей, рассмотренная система работает, как инструмент магнитно-импульсного притяжения тонкостенных листовых металлов.

To carry out numerical estimates of currents and forces in the investigated inductor system with an attractive screen (ISAS) and determine the effectiveness of the force attraction. The calculated relationships and graphical constructions were obtained using the initial data of the system: induced current in the screen and sheet metal; the distributed force of attraction (Ampère force); the repulsive force acting on the sheet metal (Lorentz force); amplitude values of the force of attraction and repulsion; phase dependence of the force of attraction, the repulsive force and the total resulting force. The results of calculations in the form of graphical dependencies of electrodynamic processes in the region under the conductors of a rectangular solenoid of inductor system with an attracting screen are presented. The graphs of forces and currents in region of dent are obtained. In the paper the analysis of electrodynamics processes for whole area under the winding of inductor system with an attractive screen is shown. The flowing this processes in the region of dent a given geometry is presented. The considered inductor system with an attractive screen and a rectangular solenoid is improved, in comparison with the previous developed ISAS. It has a working area under the lines of parallel conductors in the cross section of a rectangular solenoid, and this allows to place a predetermined portion of the sheet metal anywhere within the working region. Comparison of the indicators of electrodynamics processes in the considered variants of calculation shows an approximate growth of almost 1.5 times the power indicators in the area of the accepted dent in comparison with similar values for the entire area under the winding of the ISAS. The results obtained are important for the practice of real estimates of the excited forces of attraction. With a decrease in the dent, the amplitude of the electrodynamics forces being excited is growing proportionally (for example, when the depth decreases by 3 mm, the forces increase more than 2 times). The highest efficiency of force attraction is for sheet metal regions, the dimensions do not exceed the transverse dimensions of the winding branches of the exciting solenoid.
Numerical estimates of electrodynamics processes in the inductor system with an attractive screen and a flat rectangular solenoid
Keywords: магнитно-импульсная обработка; ток Фуко; индуктор; сила притяжения; электродинамические процессы; magnetic-pulsed treatment